Precalculus (10th Edition)

Published by Pearson
ISBN 10: 0-32197-907-9
ISBN 13: 978-0-32197-907-0

Chapter 5 - Exponential and Logarithmic Functions - Chapter Review - Cumulative Review - Page 349: 12



Work Step by Step

$4^{x-3}=8^{2x}\\(2^2)^{x-3}=(2^3)^{2x}\\2^{2(x-3)}=2^{3(2x)}\\2^{2x-6}=2^{6x}$. We know that if $x\ne1,\ne-1$ then $x^a=x^b\longrightarrow a=b$. Hence here: $2x-6=6x\\2x=6x+6\\-4x=6\\x=-\frac{3}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.